Efficacy and safety of netakimab, a novel anti-IL-17 monoclonal antibody, in patients with moderate to severe plaque psoriasis. Results of a 54-week randomized double-blind placebo-controlled PLANETA clinical trial - Luis Puig (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Background. Netakimab (NTK), an original humanized anti-interleukin-17 monoclonal antibody, showed therapeutic efficacy in moderate to severe plaque psoriasis in a phase 2 clinical study. Herein we report the results of 54 weeks of a phase 3 trial.